Analisis Tingkat Kepuasan Nasabah Atas Kualitas Pelayanan Pada PT Asuransi Jiwasraya (Persero) Semarang Timur Branch Office. - Henry Habincaran; Wahyu Hidayat; Rodhiyah Rodhiyah (Universitas Diponegoro, 2013)
Amount customers of PT. Asuransi Jiwasraya (Persero) Semarang Timur Branch Office (BO) in its development has increased and decreased. Decrease the amount identified as a loss for the company, it is very closely related to customer satisfaction over the performance of PT. Asuransi Jiwasraya (Persero) Semarang Timur Branch Office (BO) so the company needs to know the level of satisfaction and the level of corporate performance evaluation materials. Formulation of the problem in this research is how the level of client satisfaction for services on the dimensions of reliability, responsiveness, assurance, empathy and direct evidence. The conclusion of the study is on the performance expectations of customers have approached the company with a low value congruence between 69.2 percent to 91.88 percent. Overall the five dimensions of reliability, responsiveness, assurance, empathy and direct evidence have the customer satisfaction level of 3.68, which means customers are satisfied with the performance of PT Asuransi Jiwasraya (Persero) Semarang Timur Branch Office (BO).Atribut a prompt delivery service and proper regarding the issuance of a policy according to customer halpenting but less attention from the company.